Pelaksanaan Bank Garansi dalam Perjanjian Jasa Konstruksi Antara Pemerintah Daerah dengan Kontraktor (Studi pada Pemerintah Daerah dan BPD Jateng Cabang Sragen) - Purnamasari, Intan Era, Septarina Budiwati, S.H., M.H (2017)
Bank Guarantee is a guarantee given by the bank, the bank declared a written charter that it approves and attach to the insured within a specified period and certain onditions. Analysis of feasibility and the precautionary principle become a benchmark bank to avoid wanpretasi. This study aims to investigate the implementation of a Bank Guarantee in the construction services agreement between local governments and contractors. This research method using mpiricaluridical approach with primary data obtained through interviews obtained directly from BPD Central Java Sragen Branch and the Department of Public Works and secondary data from literature materials. Data were collected by field studies and literature with kualitatif.Hasil data analysis of this study indicate that (1) Mechanism of Bank Guarantee in the construction services agreement between local government and the contractor (2) The problems that occurred in the implementation of the bank guarantee.Keywords: Bank Guarantee and Wanprestasi